Single dads club - Beharrie, Therese (Montlake, 2023)
Single father Rowan Quinn moves to a tight-knit coastal community in South Africa to give his son the family he never had and meets a former heiress who makes it her personal mission to induct him into the town's circle of single dads to give him the support he needs.